PROBLEM FORMALIZATION OF POLYERGATIC TRANSPORT TECHNOLOGICAL SYSTEMS DESIGN - Melkumyan, Valter; Ostroumov, Ivan; Maliutenko, Tetiana (Proceedings of National Aviation University (archive), 2014)
The analysis of some aspects of a terminological problem of the scientific direction of the theory oftechnological systems research has carried out. Determination of concepts and terms of technological systems that willallow to use results of the researches, the latest technologies, optimum control and management systems for productionin different spheres of society activity, including in case of design and maintenance of transport systems are offeredmore expanded according to the contents.